Participação no processo coletivo brasileiro: um debate sobre legitimidade adequada no processo e representação adequada dos grupos - Gontijo, Luana Cabral Mendes (2022)
The present paper aims to make the participation declared by the Democratic State of Law compatible with the collective process model adopted by the Brazilian legal system, which is proposed through the combination of mechanisms that aim to control the adequate standing in the process and adequate representation of groups. Thus, the objective is to combine the model of extraordinary standing by procedural substitution of the member of the group by a qualified member with participation of groups promoted through proper techniques used in the procedures, in order to contribute to a fair resolution of the class action. In the first chapter, it analyzes participation as a fundamental element for the development of the Democratic State of Law, as well as its manifestation within the Judiciary as the right to be heard. The inflows of participatory democracy are discussed in the understanding of the right to be heard, which ceases to have a merely formal function and objetive the promotion of effective participation in the exercise of judicial activity. Then, the right to be heard is analyzed on the scope of the collective process, considering the dissociation between the qualified claimant and the right holder. In the second chapter, the standing model adopted in the Brazilian collective process is analyzed in order to understand the relationship between qualified claimant and the protected group. In the third chapter, we proceed with a constitutionalized analysis of collective standing that recognizes autonomy to the qualified claimant, at the same time that it imposes that their performance is not disconnected from the interests of the group. For that, we adopted the proposal of splitting the expression adequacy of representation into two others: adequate standing and adequate representation. We also discuss the diversification of the means of solving collective conflicts, especially the use of agreement techniques, as a means of implementing participation and carrying out the fair protection of the right, observing concepts of adequate standing and adequate representation. Finally, it is concluded that the model of standing in collective redress in Brazil is essential to enable the protection of the rights of groups, remaining as the main technique of participation in the collective redress, however it is complemented by other mechanisms of participation that guarantee that the action of the qualified claimant is consistent with reality. In short, it is recognized that the right to be heard needs to go beyond the dialogue between the parties, making the process a democratic environment that allows the influence of the groups – the main ones affected by the collective decision – in the construction of the decision.